Leadership styles and leadership outcomes in nursing homes: a cross-sectional analysis - Joris Poels; Marc Verschueren; Koen Milisen; Ellen Vlaeyen (BMC Health Services Research, 2020)
Abstract Background Although leadership is considered as a key factor in health care, leadership styles and outcomes in nursing homes often remain a black box. Therefore, this study explored leadership styles and leadership outcomes of head nurses and directors of nursing (DoN) in nursing homes based on well-defined leadership concepts. Methods A multicenter cross-sectional analysis was conducted on baseline data of an ongoing cohort study comprising a convenience sample of nursing home staff (n = 302). Leadership styles and leadership outcomes of head nurses and DoN were measured through the rater form of the Multifactor Leadership Questionnaire 5X (MLQ-5X). Based on the Full Range of Leadership Model, the MLQ-5X visualizes transformational (relation and change focused), transactional (task-focused) and passive-avoidant (absence of leadership) leadership styles. Scores of head nurses and DoN for leadership styles and outcomes were compared with European Reference Scores (ERS) using two-sided one-sample t-tests. Results Compared with ERS, head nurses and DoN scored significantly lower (p < 0.001) on transformational and transactional leadership styles and significantly higher (p < 0.001) on passive-avoidant leadership styles. All leadership outcomes were significantly lower (p < 0.001) for head nurses. Similar results, however not statistically significant, were found concerning leadership outcomes of DoN. Conclusions Results indicate that passive-avoidant leadership styles are excessively present in contrast to transformational leadership styles in nursing homes. This highlights an urgent need to invest in leadership development. Therefore, future research should focus on interventions for the development of transformational leadership.